Collagen 2A Type B Induction after 3D Bioprinting Chondrocytes In Situ into Osteoarthritic Chondral Tibial Lesion. (December 2021) - Gatenholm, Birgitta; Lindahl, Carl; Brittberg, Mats; Simonsson, Stina
Objective: Large cartilage defects and osteoarthritis (OA) cause cartilage loss and remain a therapeutic challenge. Three-dimensional (3D) bioprinting with autologous cells using a computer-aided design (CAD) model generated from 3D imaging has the potential to reconstruct patient-specific features that match an articular joint lesion. Design: To scan a human OA tibial plateau with a cartilage defect, retrieved after total knee arthroplasty, following clinical imaging techniques were used: (1) computed tomography (CT), (2) magnetic resonance imaging (MRI), and (3) a 3D scanner. From such a scan, a CAD file was obtained to generate G-code to control 3D bioprinting in situ directly into the tibial plateau lesion. Results: Highest resolution was obtained using the 3D scanner (2.77 times more points/mm 2 than CT), and of the 3 devices tested, only the 3D scanner was able to detect the actual OA defect area. Human chondrocytes included in 3D bioprinted constructs produced extracellular matrix and formed cartilage tissue fragments after 2 weeks of differentiation and high levels of a mature splice version of collagen type II (Col IIA type B), characteristic of native articular cartilage and aggrecan (ACAN). Chondrocytes had a mean viability of 81% in prints after day 5 of differentiation toward cartilage and similar viability was detected in control 3D pellet differentiation of chondrocytes (mean viability 72%). Conclusion: Articular cartilage can be formed in 3D bioprints. Thus, this 3D bioprinting system with chondrocytes simulating a patient-specific 3D model provides an attractive strategy for future treatments of cartilage defects or early OA.